1965
DOI: 10.1136/hrt.27.2.151
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Isolated Pulmonary Stenosis

Abstract: The natural history of isolated pulmonary stenosis is largely unknown. Knowledge of this subject has been gained mostly from studying groups of patients of different ages, or from necropsy records, procedures clearly less satisfactory than following up individual cases. Only two authors have reported follow-up studies; Barritt (1954) observed 33 cases (8 have been catheterized) over periods of 5 to 21 years, and Fabricius (1959) followed up 47 of 75 fully-documented cases for periods of between 2 and 10 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Consequently, exercise capacity is reduced due to an inability to increase stroke volume with the increase in heart rate being the sole contributor to an increase in cardiac output 5 6. Conversely, the natural evolution of mild PV stenosis is considered to be benign without progression of the valve gradient after adolescence and no deaths are observed during an 8-year follow-up period 3 7. Because of this, no restrictions in physical activity are imposed 8 9…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, exercise capacity is reduced due to an inability to increase stroke volume with the increase in heart rate being the sole contributor to an increase in cardiac output 5 6. Conversely, the natural evolution of mild PV stenosis is considered to be benign without progression of the valve gradient after adolescence and no deaths are observed during an 8-year follow-up period 3 7. Because of this, no restrictions in physical activity are imposed 8 9…”
Section: Introductionmentioning
confidence: 99%
“…T inker et al [8] reported the follow-up of 59 cases. No evidence of deterioration was found in the patients with mild or moderate stenosis, three of whom had a second cardiac catheterization after intervals of 6-8 years when considerable growth occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is widely used in severe and moderate cases, and only few long-term follow-up studies have been reported [1][2][3][4][5][6][7][8]. In 1959 F abricius [3] from this laboratory published his monograph on 75 fully documented cases.…”
mentioning
confidence: 99%
“…4 Moreover, mortality vastly differs between the groupshigh in iPAH and very low in PS. 4,5 Although the duration and possibly character of increased RV pressure differs between the two conditions, the RV response also seems very different. A study by Jurcut et al 7 demonstrated this difference in adult iPAH and PS patients, showing global RV dilation and decreased global RV free wall (RVFW) longitudinal deformation in iPAH vs PS patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 While a large proportion of iPAH patients present with, or rapidly develop, symptomatic heart failure, 5,6 PS patients are often asymptomatic or present with only mild exercise intolerance. 4 Moreover, mortality vastly differs between the groupshigh in iPAH and very low in PS. 4,5 Although the duration and possibly character of increased RV pressure differs between the two conditions, the RV response also seems very different.…”
Section: Introductionmentioning
confidence: 99%